1996
DOI: 10.1097/00007632-199603150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Are Occupational Drivers at an Increased Risk for Developing Musculoskeletal Disorders?

Abstract: Vibration (resulting from driving) and lifting cause back, neck, and shoulder pain, whereas inability to work seems affected by stress at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
1
11

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(156 citation statements)
references
References 29 publications
11
133
1
11
Order By: Relevance
“…Four out of six studies showed a moderate positive association (average OR=2.1) between sitting and LBP [7,9,22,44]. The remaining two studies found an almost null association between professional driving and LBP [6,53].…”
Section: Lbpmentioning
confidence: 88%
See 1 more Smart Citation
“…Four out of six studies showed a moderate positive association (average OR=2.1) between sitting and LBP [7,9,22,44]. The remaining two studies found an almost null association between professional driving and LBP [6,53].…”
Section: Lbpmentioning
confidence: 88%
“…Bus drivers were the subject of two separate studies. Although the OR in both studies was not equal, both studies showed a positive association between sitting and reported LBP ( ‡1.5) [9,44]. In fact, Bovenzi and Zadini [9] reported an OR of 2.57 (95% CI 1.52-4.35) while Magnusson et al [44] reported an OR of 1.79 (95% CI 1.16-2.75).…”
Section: Lbpmentioning
confidence: 89%
“…Low job satisfaction was suggested to be associated with back complaints (39,53,56,57) in the cross-sectional studies although null associations were found in surveys among professional drivers and firefighters (44,46). In a prospective study among aircraft workers, the employee's job dissatisfaction was found to be the strongest predictor of subsequent back injury, with a relative risk of 1.70 and an attributable fraction of 41%.…”
Section: Psychological Risk Factorsmentioning
confidence: 96%
“…19 This is explained not only by the above-mentioned mechanical factors but also by the presence of stress to which drivers are subjected in general, triggering musculoskeletal pain. 20,21 Thus, given the high incidence of low back pain and the high costs of its consequences, studies have been conducted to estimate the most effective measures to control symptoms, although preventing the onset of low back pain can be more efficient and cost-effective. This requires knowledge of the triggering factors and the profile of the individuals who are more susceptible to the onset of low back pain.…”
Section: Introductionmentioning
confidence: 99%